Measuring effectiveness of ticketing services of public transportation. (17th September 2021) - Srivastava, Govind Nath; Purohit, Harsh
Public transport services are going through transition phase across the globe due to changes in the market dynamics and growing expectation of commuters. As ticketing services of public transport organisation has abiding impact over ridership behaviour, public transport organisations are using innovative, customer centric and cost effective strategy to offer convenient, attractive and speedy ticketing solution to commuters. The current study has been undertaken to analyse effectiveness of each element of ticketing services of Delhi Metro over commuter's satisfaction. Both qualitative and quantitative research approach was used and Nivivo 11, SPSS.20 software was employed for identification of important issues and processing of the data. The result of the study reveals that commuters are highly sensitive about price of the ticket and long waiting time in a queue and suffocation at ticket counter is adversely influencing satisfaction of commuters.